Antifungal evaluation of fengycin isoforms isolated from Bacillus amyloliquefaciens PPL against Fusarium oxysporum f. sp. lycopersici. (December 2020) - Kang, Beom Ryong; Park, Joon Seong; Jung, Woo-Jin
Abstract: Bacillus amyloliquefaciens PPL is known to have a broad spectrum antifungal activity against plant pathogenic fungi. We focused on the cyclic lipopeptides (CLPs) extracted from the culture broth that are known to promote the ability and the efficiency of B. amyloliquefaciens PPL to control fungal diseases in pepper and tomato. In this study, the PPL strain exhibited enhanced culture yield and increased production of fengycin lipopeptides upon lecithin supplementation. The purified iturin A fraction from strain PPL exhibited higher antifungal activity (73 – 80%) against pepper anthracnose than fengycin fraction in vitro and in vivo . However, the control of tomato Fusarium wilt by the PPL strain was mainly attributed to fengycin lipopeptides. A comparison of liquid chromatography-mass spectrometry (LC-MS) and LC-tandem MS analysis of the filtrate, we found that the antifungal compounds against Fusarium wilt present in the strain PPL culture filtrate were a series of isoforms of fengycin (type F1, F2, and F3). The purified fengycin F1 type showed better antifungal activity against Fusarium wilt compared the other isoforms. To the best of our knowledge, this is the first study to report the antifungal activity of fengycin isoform types in the context of Fusarium wilt. The CLPs produced by the PPL strain are potential candidates for controlling fungal disease in tomato and pepper plants. Highlights: The culture medium upon lecithin supplementation improved the biomass and functions of B. amyloliquefaciens PPL. Bacillus amyloliquefaciens PPL produced the three types of cyclic lipopeptides. The purified iturin A suppressed the development of pepper anthracnose disease. Bioactive peptides of fengycin contributed to the improved antifungal potential against tomato Fusarium wilt.